Empirical study on temporal variations of canopy-level Urban Heat Island effect in the tropical city of Greater Kuala Lumpur - Ramakreshnan, Logaraj; Aghamohammadi, Nasrin; Fong, Chng Saun; Ghaffarianhoseini, Amirhosein; Wong, Li Ping; Sulaiman, Nik Meriam (Elsevier, 2019)
A very few studies have evaluated and understood the temporal dynamics of UHI in many expanding tropical cities. Hence, this study investigated the temporal variations of canopy-level UHI in selected urban stations, namely Petaling Jaya (PJ) and Subang (SUB), of Greater Kuala Lumpur (GKL) using 2016’s hourly data set obtained from meteorological observatories. The association between meteorological factors and UHI Intensity (UHII) is evaluated using linear regression models and Pearson correlation analysis. The findings revealed positive thermal contrasts between urban and sub-urban stations with maximum UHII during dry, southwest monsoon season in PJ (June: 1.68 °C) and SUB (August: 1.29 °C) stations respectively. PJ station exhibited a distinct diurnal cycle with the maximum nocturnal UHII of 1.71 °C at about 8 p.m. after sunset under ideal meteorological conditions. The results also demonstrated that UHI events occurred more frequently at nights in urban stations in the magnitude range of 0–2 °C. Cooling at all urban sites starts around 2–3 p.m. with the highest rate of 0.73 °C/h and 0.96 °C/h in PJ and SUB stations. Meanwhile, relative humidity displayed a low positive correlation (r = 0.37, p ≥ 0.05) and a high negative correlation (r = −0.79, p < 0.05) with UHII in PJ and SUB stations respectively. The influence of wind speed on UHII is weak (r = −0.44, p < 0.05) in PJ station and strong (r = 0.83, p < 0.05) in SUB station. Overall, this study can be regarded as one of the comprehensive observational investigations of canopy-level UHI in a tropical city that provide vital inputs to enrich the tropical urban climate literacy.